LIBASUTTAQWA IN THE POEM OF SIDI DJAMADI: A HERMENEUTIC STUDY OF PAUL RICOEUR - Wachid Eko Purwanto; Yosi Wulandari (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2019)
Poem Sidi Djamadi is one of the poems of the Minangkabau which contains Islamic teachings. This study aims to describe the concept of clothing in the poem Sidi Djamadi and clothing as a representation of piety in the poem Sidi Djamadi. This poem was written by Shaykh Sidi Djamadi as a transmitter of Islamic teachings. This poem is examined by Paul Ricoeur's hermeneutic approach. This research uses Paul Ricoeur's hermeneutics approach. The object of research is the poem Sidi Djamadi. The research subject is clothing as a representation of piety. Data obtained through transliteration, data inventory, analysis and interpretation, and conclusions. The results of this study are Syair Sidi Djamadi has two concepts of clothing, namely outerwear and inner clothes. Birth clothes are clothes cover genitalia. Clothing as a representation of aurat cover is complete clothing, clothing that functions as a cover of aurat. This type of clothing has many kinds. Daily clothing, special worship clothing (ihram cloth for Hajj and Umrah) and fi sabilillah war clothing. These three kinds of clothes were born to cover the nakedness and support the worship. Inner clothing is the concept of piety clothing (libas attaqwa). The concept of inner clothes consists of five types of representations. The five types of representation are clothing as a representation of faith, clothing as a representation of righteous deeds, clothing as a representation of a good way of life, clothing as a representation of concern for the torment of God, and clothing as a representation of shame.